Design, Synthesis, and Characterization of Polyphosphazene Bearing Stable Nitroxide Radicals as Cathode‐Active Materials in Li‐Ion Batteries. Issue 17 (8th June 2017) - Yeşilot, Serkan; Hacıvelioğlu, Ferda; Küçükköylü, Sedat; Çelik, Kamile Burcu; Sayan, Gürkan; Demir‐Cakan, Rezan
Abstract : A new and facile synthetic strategy is developed for the synthesis of a polyphosphazene bearing stable nitroxide radicals as a cathode‐active material for rechargeable lithium batteries, which performs over 80 mAh g −1 capacity at a C/2 current density for 50 cycles. Abstract : A new synthetic strategy is developed for the synthesis of polyphosphazene bearing stable nitroxide radicals as a pendant group. The resulting material is investigated as a cathode‐active material for rechargeable lithium–ion batteries that performs 80 mAh g −1 capacities at a C/2 current density over 50 cycles. Thus, the inorganic–organic hybrid system can be proposed as an alternative cathode‐active material with improved performance.